Analysis of Locutionary Speech Acts in the Comment Column of Olshop Accounts on Instagram - Windy; Yusni Khairul Amri; Dian Marisha Putri (Britain International for Academic Research (BIAR) Publisher, 2023)
Instagram has expanded into a business area which is a way to promote and sell products or goods to other Instagram users which is commonly called an online shop. This analysis aims to describe the locutionary speech acts contained in the comments column of the olshop account on Instagram. The data sources in this analysis are several olshop accounts on Instagram. In this analysis, data were analyzed using locutionary speech acts, namely speech acts that state something. According to Chaer and Agustina, locutionary speech acts are divided into three, namely locutionary speech acts in the form of questions, locutionary speech acts in the form of statements, and locutionary speech acts in the form of orders. From the results of the analysis of the twenty data collected, there were 13 data included in the three locutionary speech acts, namely 9 data including locutionary speech acts in the form of questions, 2 data including locutionary speech acts in the form of statements, and 2 data which includes locutionary speech acts in the form of commands.